Noradrenaline reuptake inhibitors limit neuroinflammation in rat cortex following a systemic inflammatory challenge: implications for depression and neurodegeneration. - HARKIN, ANDREW; CONNOR, THOMAS JOSEPH; RYAN, KAREN MARGARET (Cambridge University Press, 2009)
Evidence suggests that noradrenaline has a tonic anti-inflammatory action in the central nervous system (CNS) via its ability to suppress microglial and astrocytic activation, and inhibit production of inflammatory mediators. Consequently it is suggested that noradrenaline may play an endogenous neuroprotective role in CNS disorders where inflammatory events contribute to pathology. Here we demonstrate that acute treatment of rats with the noradrenaline reuptake inhibitors (NRIs) desipramine and atomoxetine elicited anti-inflammatory actions in rat cortex following a systemic challenge with bacterial lipopolysaccharide (LPS). This was characterized by a reduction in cortical gene expression of the pro-inflammatory cytokines interleukin-1 (IL-1) and tumour necrosis factor- (TNF-), the enzyme inducible nitric oxide synthase (iNOS), and the microglial activation markers CD11b and CD40. These anti-inflammatory actions of NRIs were associated with reduced activation of nuclear factor-kappa B (NF-B); a transcription factor that is considered the major regulator of inflammation in the CNS. To determine whether NRI administration directly altered glial expression of these inflammatory markers, primary cortical glial cells were exposed in vitro to the NRIs desipramine or atomoxetine. In vitro treatment with NRIs largely failed to alter mRNA expression of IL-1, TNF-, iNOS, CD11b and CD40, following stimulation with LPS. Similarly, LPS-induced TNF- and IL-1 protein production from glial cells was unaffected by NRI treatment. In contrast, in vitro exposure of cultured glial cells to noradrenaline suppressed IL-1, TNF-, iNOS and CD40 expression. These results suggest that in vivo administration of NRIs limit inflammatory events in the brain, probably by increasing noradrenaline availability. Overall, this study has yielded significant insights into the ability of noradrenaline- augmentation strategies to limit neuroinflammation.
PUBLISHED
Keywords: Neurosciences; noradrenaline